A Study on the Optometrist’ Images between Major Students and Non-major Students (Medico Legal Update, 2020)
Background/Objectives: This study was designed to assess the actual state of optometrist’ image, to determine their identity, and to provide fundamental feedback to improve their image.Method/Statistical Analysis: The study involved 303 students, 179 of whom were majoring in optometry, while 124 were not. The subjects were asked to answer an online questionnaire survey in order to analyze optometrist’ images. The collected data were compared and analyzed at a significance level of 0.05 using SPSS 18.0.Findings: In terms of optometrist’ general image, optometry major students rated it 3.75, while non-major students gave it 4.02 points (p